Plasma folate and vitamin B12 levels in beta-thalassemia heterozygotes. - Silva, A. E.; Varella-Garcia, M. (My University, 1989)
Plasma folic acid and vitamin B12 levels of 21 heterozygous beta-thalassemic patients from São José do Rio Preto, SP, Brazil did not differ from those of family member controls or of controls matched for age, sex and socioeconomic status. All values were within the normal range for folic acid (3-17 ng/ml) and vitamin B12 (200-950 pg/ml). A highly significant positive correlation (P less than 0.01) between folic acid and B12 levels was observed both in thalassemic patients (r = 0.93) and in the controls (r = 0.97).